Robotics in Spinal Surgery: Current Limitations and Future Directions - Phung, Justin (The Meducator, 2022)
Surgical robotics have been introduced in a number of disciplines, with the aim of minimizing tissue disruption, reducing operating personnel radiation exposure, and improving dexterity and efficiency relative to human operation. In spinal surgery, robotic systems are relatively novel, applied to date largely for the placement of pedicle screw instrumentation. Only a few robotic systems have been approved for spinal surgery, and there remain significant barriers to the widespread implementation of surgical robotic techniques. This review provides an overview of robotic systems in spinal surgery and identifies current limitations that must be addressed before clinical use, including clinical merit relative to freehand navigation systems, steep learning curves, and unclear cost-effectiveness.